Kidlat a diesel hybrid vehicle - Lao, Ervian (Philippine Engineering Journal)
This study came up with a solution to the rising fuel prices by designing and building the Philippines' first diesel-hybrid car. A hybrid vehicle combines a conventional internal combustion engine propulsion system with an electric propulsion system. The output aims to achieve better fuel efficiency compared with conventional automotive vehicles. The study used a series hybrid power train where only the electric motor drives the drive train, while the internal combustion engine acts as generator to power the electric motor. With the diesel engine running at its most efficient state, fuel efficiency increased exponentially while maintaining the speed required of a typical vehicle. The study also designed and fabricated an aerodynamic body, reducing air drag and further improving fuel efficiency. The whole project lasted around six months. The researchers designed the automotive chassis and body during the first two months. The remaining time was used to construct the vehicle itself. When the automobile was tested in Sepang, Malaysia, the results showed that it can run up to 59.9 km/l. Compared to typical cars running on average of 10 km/l. the diesel hybrid car designed by the researcheres registered almost six times more. The results of the study opened possibilities for consumers saving at least Php4.00 per kilometer. These are big savings especially now that fuel prices are always increasing.